Environmental Technologies to Treat Sulphur Pollution: Principles and Engineering 2020
DOI: 10.2166/9781789060966_0133
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and sulfur-related bacteria

Abstract: Concrete and carbon steel are among the most used materials in many industries, such as infrastructure, transportation and manufacturing. Surfaces of both materials, when exposed to non-sterile environments, can be the sites of biological activities of various microorganisms. Many of the activities are deleterious. From the long-term perspective, both concrete and metal can deteriorate and may ultimately lose their original functionalities. The deterioration of materials caused by microorganisms is known as mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…In the bottom of the flasks, where there is hardly any oxygen, reduction reactions of sulfates or of sulfur itself occur, resulting in the generation of H 2 S and metal sulfides after combining sulfides with leached metals-especially iron-from the steel bars. Hydrogen sulfide is highly corrosive [37][38][39], which would explain the deep damage observed in the steel samples. Figure 5 summarizes the proposed hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the bottom of the flasks, where there is hardly any oxygen, reduction reactions of sulfates or of sulfur itself occur, resulting in the generation of H 2 S and metal sulfides after combining sulfides with leached metals-especially iron-from the steel bars. Hydrogen sulfide is highly corrosive [37][38][39], which would explain the deep damage observed in the steel samples. Figure 5 summarizes the proposed hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lower mass loss (less than 5 wt.%) of the GP/GGBS-rich AAMs was associated with the amount of bio lm growth. To some extent, the bio lm formation located on the AAMs mortar surface would provide a protective barrier reducing the transmission of corrosive substances into the sewage [31,35]. On the other hand, the mass loss of AAMs increased with the increase of the ISSA content, and the maximum mass loss (about 17.8%) was found in the sample prepared with 100% ISSA.…”
Section: Change In Mass After Sewage Corrosion Testmentioning
confidence: 99%
“…It had been reported that when the pH value was lowered to ∼9, the microbial communities (e.g. SOB) would develop and oxidize H 2 S(g) to sulfuric acid in the presence of su cient moisture, nutrients and oxygen [31]. After 7 days, the pH dropped to around 5.0, meaning a formation of a weak acid environment in the chamber due to chemical and biological processes, happening in the solution.…”
Section: Characteristics Of Arti Cially Intensi Ed Sewagementioning
confidence: 99%